New insights into transparent exopolymer particles (TEP) formation from precursor materials at various Na+/Ca2+ ratios - Meng, Shujuan (2018)
Transparent exopolymer particles (TEP) are planktonic, organic microgels which play significant roles in cycling of carbon and trace elements, aggregation of particles, feeding and accommodating microbes as well as development of biofilms. However, few studies are available on the mechanism of TEP formation in various water environments. Here we investigate the formation of TEP with alginate blocks as precursors at various Na+/Ca2+ ratios to simulate the situations in different aquatic environments (e.g. freshwater and seawater). We found that the formation of TEP from precursor materials studied was essentially determined by the Ca2+ concentration at a fixed sodium concentration, while Na+ at high Na+/Ca2+ ratio out-competed Ca2+ for the binding sites on the precursor molecules, leading to a significantly decreased trend of TEP formation. Our results indicate that a more abundant TEP could be expected in freshwater than in seawater, and we also discuss the engineering implications of the findings.